Progress of research on management of skin graft-versus-host disease following allogeneic hematopoietic stem cell transplantation (异基因造血干细胞移植皮肤急性移植物抗宿主病管理的研究进展) - FU Yuxin (符玉欣); ZHOU Ting (周婷) (中西医结合护理, 2023)
Hematopoietic stem cell transplantation (HSCT) is an important method for the treatment of malignant and non-malignant refractory hematologic diseases. Graft-versus-host disease (GVHD) is one of the main complications, which seriously affects the prognosis of patients. By reviewing of related studies, this paper summarized pathogenesis, clinical classification, prevention and treatment and nursing measures of acute skin graft-versus-host disease(aGVHD) following allogeneic HSCT, and put forward relevant management advice, in order to provide reference for clinical nurses in the early period of prevention, early detection and timely intervention on aGVHD. (造血干细胞移植是目前治疗恶性及非恶性难治性血液病的重要方法, 移植物抗宿主病(GVHD)是其主要并发症之一, 严重影响患者预后。本研究通过查阅国内外相关文献, 综述异基因造血干细胞移植皮肤急性移植物抗宿主病(aGVHD)的发病机制、临床分级、预防、治疗和护理措施, 并提出相关管理建议, 以期协助临床医护人员针对皮肤aGVHD的前期预防、早期发现、及时干预提供参考。)